Maltodextrin stimulates growth of Bacillus cereus and synthesis of diarrheal enterotoxin in infant milk formulae. - Rowan, N J (1997)
One hundred reconstituted milk-based infant formulae (IMF) representative of 10 leading brands available in many European Economic Community countries were examined for Bacillus cereus and for the presence of diarrheal enterotoxin. Sixty-three reconstituted IMF supported growth of the organism after 14 h at 25 degrees C, and in 4 of these, which contained maltodextrin, enterotoxin was detected. Reconstituted IMF (and basal synthetic media) supplemented with > or = 0.1% maltodextrin supported both growth of B. cereus and diarrheal toxin production when incubated for 14 h or more at 25 degrees C.